Evaluating a community health nursing internship using the Kirkpatrick four-level model: Evidence from Iran - Yousefi, Mahboubeh Sadat; Dehghan, Mohsen Fooladzadeh; Hosseini, Meimanat; Jokar, Mozhgan; Khajoei, Rahimeh; Najafi, Mitra; Salemian, Hamed (REID (Research and Evaluation in Education), 2025)
This study aimed to evaluate the effectiveness of a community health nursing internship course for final-year nursing students in comprehensive health centers in Tehran, Iran, using Kirkpatrick’s four-level model. The evaluation was performed in terms of the reaction, learning, behavior and outcomes dimensions based on the Kirkpatrick 4-level model. Fifty-six nursing students and 180 clients were randomly selected. Data were collected through researcher-made questionnaires and checklists and analyzed using descriptive and analytical statistical tests. At Level 1, students’ overall satisfaction averaged 61, with the highest satisfaction in clinical instructor performance (77.53%). At Level 2, the mean self-evaluation learning score was 66.29; the highest learning occurred in vaccination (89.28%) and growth monitoring/ supplementary nutrition (69.64%). The overall performance evaluation averaged 70.14, with vaccination scoring the highest (91.07%). Clients reported high satisfaction with the care provided by students (Level 4 mean: 72.99). No significant association was found between students’ demographic characteristics and the first three levels of the model. The internship demonstrated effectiveness at all four Kirkpatrick levels. The findings support the value of structured community health internships and highlight the need for educational authorities to develop a standardized, evidence-based program that addresses the identified strengths and areas for improvement.